2010
DOI: 10.1016/j.jasms.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The study of protein conformation in solution via direct sampling by desorption electrospray ionization mass spectrometry

Abstract: The direct sampling feature of liquid sample desorption electrospray ionization (DESI) allows the ionization of liquid samples without adding acids/organic solvents (i.e., without sample pretreatment). As a result, it provides a new approach for probing protein conformation in solution. In this study, it has been observed that native protein ions are generated from proteins in water by DESI. Interestingly, the intensities of the resulting protein ions appear to be higher than those generated by ESI of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 41 publications
3
53
0
Order By: Relevance
“…However, there are experiments which demonstrate that mildly denaturing conditions may not be sufficient to enable protein unfolding within the timescale of ESI. Liquid desorption electrospray ionization, or liquid DESI, developed by the Chen group, [20] can be used to introduce the analyte of interest independently from the ionization solution as shown in Figure 2a. For example, an aqueous myoglobin solution can be intersected with an ionized plume of water/methanol/ acetic acid (50/50/1).…”
Section: Timescalementioning
confidence: 99%
“…However, there are experiments which demonstrate that mildly denaturing conditions may not be sufficient to enable protein unfolding within the timescale of ESI. Liquid desorption electrospray ionization, or liquid DESI, developed by the Chen group, [20] can be used to introduce the analyte of interest independently from the ionization solution as shown in Figure 2a. For example, an aqueous myoglobin solution can be intersected with an ionized plume of water/methanol/ acetic acid (50/50/1).…”
Section: Timescalementioning
confidence: 99%
“…1, 5 of CTH in bulk reaction mixtures (reaction time of a few minutes) (15). Ambient ionization methods (24)(25)(26) such as desorption electrospray ionization (DESI) (27)(28)(29) provide a simpler approach to intercepting reactive species without prior sample preparation (30)(31)(32)(33)(34)(35). We recently demonstrated that DESI can intercept CTH intermediates in solution on the millisecond time scale (36).…”
mentioning
confidence: 99%
“…The ionization occurs via the interaction of liquid sample with charged droplets generated by the DESI spray and the resulting ions are collected and analyzed by a mass spectrometer. It is useful in directly analyzing samples including large proteins/protein complexes from their native environments [16,[29][30][31][32][33][34]. Furthermore, it is possible to use liquid sample DESI-MS for studying fast reaction kinetics in submillisecond time resolution [35] or coupling with liquid chromatography (LC) [18,[36][37][38], microfluidics [26], and microextraction [39].…”
Section: Introductionmentioning
confidence: 99%